2010
DOI: 10.1177/1084713810375567
|View full text |Cite
|
Sign up to set email alerts
|

Cued Speech for Enhancing Speech Perception and First Language Development of Children With Cochlear Implants

Abstract: Nearly 300 million people worldwide have moderate to profound hearing loss. Hearing impairment, if not adequately managed, has strong socioeconomic and affective impact on individuals. Cochlear implants have become the most effective vehicle for helping profoundly deaf children and adults to understand spoken language, to be sensitive to environmental sounds, and, to some extent, to listen to music. The auditory information delivered by the cochlear implant remains non-optimal for speech perception because it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 73 publications
4
42
0
2
Order By: Relevance
“…Early exposure to audio-visual speech is critical to develop balanced speech perception multi-modal brain networks (Schorr, Fox, van Wassenhove, & Knudsen, 2005). Accordingly, we and others previously showed that early and intensive exposure to cued speech enhances speech perception (Leybaert & LaSasso, 2010), phonemic awareness and reading skills in children with a Cl Colin et al, 2010). Once phonological representations become sufficiently accurate, children could progressively switch to purely auditory speech learning.…”
Section: Discussionmentioning
confidence: 91%
“…Early exposure to audio-visual speech is critical to develop balanced speech perception multi-modal brain networks (Schorr, Fox, van Wassenhove, & Knudsen, 2005). Accordingly, we and others previously showed that early and intensive exposure to cued speech enhances speech perception (Leybaert & LaSasso, 2010), phonemic awareness and reading skills in children with a Cl Colin et al, 2010). Once phonological representations become sufficiently accurate, children could progressively switch to purely auditory speech learning.…”
Section: Discussionmentioning
confidence: 91%
“…Our search returned five studies to date that have tested audiovisual integration at the phoneme level in adults with cochlear implants (Agelfors 1996; Desai et al 2008; Leybaert et al 2010; Rouger et al 2008; Strelnikov et al 2009). Taken together, these studies have shown consistent improvement in phoneme perception (15- to 20-percentage points) under audiovisual conditions when compared with unimodal perception in quiet.…”
Section: Speech Perception With Cismentioning
confidence: 99%
“…Cochlear implants improve literacy skills and their benefits are greater if the child is exposed earlier to oral communication (Connor, Craig, Raudenbush, Heavner & Zwolan, ; Geers, Mitchell, Warner‐Czyz et al ., ). Other strategies, such as cued speech, have been applied to increase learning performance and ultimately improve literacy skills (Colin, Ecalle, Truy, Lina‐Granade & Magnan, ; Leybaert & La Sasso, ).…”
Section: Introductionmentioning
confidence: 99%